(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the efficacy of the “Dưỡng Nhan” herbal facial mask in treating melasma in women at the Dermatology Department – Tue Tinh Hospital in 2024. Subjects and Methods: This was a clinical interventional study conducted on 30 female patients with melasma at Tue Tinh Hospital from March to August 2024. The therapeutic outcomes of the “Dưỡng Nhan” herbal mask were evaluated based on clinical and paraclinical indicators, as well as assessments of adverse effects. Results: After 12 weeks of treatment, the mean MASI score significantly decreased from 6.68 to 3.25, with a statistically significant difference (p < 0.001), while the L* value (indicating skin brightness) showed a marked increase. Clinically, 86.6% of patients showed good to excellent improvement. The rate of adverse reactions was very low, with only one case (3.3%) experiencing mild irritation, which resolved completely. Notably, 90% of the patients reported satisfaction and felt confident during the treatment process. Conclusion: The “Dưỡng Nhan” herbal facial mask is a safe and effective therapy for improving skin pigmentation in melasma after 12 weeks of use. This herbal formulation presents high potential for clinical application and offers a new direction in the development of traditional medicine-based skincare products.